An artificial SEI material and its preparation and application in metal lithium negative electrode

The high-temperature stable SEI material produced by composite polymerization reaction on the negative electrode surface of the metal lithium battery solves the problem of thermal runaway and poor circulation performance at high temperatures, and achieves higher energy density and battery safety.

CN115498187BActive Publication Date: 2025-03-14CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211051708.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2025-03-14
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

Metal lithium batteries have a risk of thermal runaway at high temperatures, and their cycling performance is not ideal, which cannot meet the energy density requirements of large equipment.

Method used

By polymerizing the monomer of Formula 1 and the monomer of Formula 2 under an initiator, an artificial SEI material was prepared and composited on the surface of the metal lithium negative electrode to construct a stable SEI film at high temperature.

Benefits of technology

It significantly improves the high-temperature cycle stability and safety of metal lithium batteries, extends the cycle life of the battery, and improves the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115498187B_ABST
    Figure CN115498187B_ABST
Patent Text Reader

Abstract

The present invention provides a technical field of negative electrode protection for lithium metal batteries, and specifically relates to a method for preparing an artificial SEI material, wherein monomers of formula 1 and formula 2 are subjected to polymerization reaction under an initiator to prepare the artificial SEI material. The present invention also includes the SEI prepared by the preparation method and its application. The present invention has found that the innovative use of monomers of formula 1 and formula 2 to initiate polymerization can construct a new polymer network, which unexpectedly has excellent high temperature resistance. The innovative compounding of the polymer network on the surface of the metal lithium negative electrode can increase the thermal runaway temperature and effectively improve the cycle stability of the metal lithium battery at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy devices, and specifically relates to the technical field of lithium negative electrode protection for lithium metal batteries. Background Art

[0002] As awareness of environmental and energy crises continues to grow, the field of new energy has gradually become a hot topic in recent years, and battery materials have also received more and more attention. At present, the energy density of lithium-ion batteries using graphite as the negative electrode cannot meet the needs of large-scale equipment such as electric vehicles. Lithium metal has a high theoretical specific capacity (3860mAh / g), the lowest electrode potential (-3.040V vs.SHE) and a low density (0.53g / cm 3 ), is an ideal negative electrode material in lithium batteries. The potential safety hazards caused by the high activity of the metal limit its commercial application. If thermal abuse occurs during use, the SEI film on the surface of the lithium metal negative electrode will decompose and release a large amount of heat, causing the battery to go into thermal runaway. There are currently many ways to improve lithium metal batteries: modification of the electrolyte, application of flame retardant diaphragms, application of solid electrolytes, etc. If a SEI film that remains stable at high temperatures can be constructed on the surface of the negative electrode, the safety of the lithium metal battery will be effectively improved. Summary of the invention

[0003] The first object of the present invention is to provide a method for preparing an artificial SEI material, aiming to improve the stability of the prepared artificial SEI material at high temperatures.

[0004] The second purpose of the present invention is to provide an artificial SEI material prepared by the preparation method and its application in the protection of negative electrodes of lithium metal batteries.

[0005] The third object of the present invention is to provide a metal lithium negative electrode and a metal lithium battery composited with the artificial SEI material.

[0006] The thermal runaway temperature of metal lithium batteries is low, and the cycle performance at high temperatures is not ideal. To address this problem, the present invention provides the following solutions:

[0007] A method for preparing an artificial SEI material, comprising subjecting a monomer of formula 1 and a monomer of formula 2 to a polymerization reaction under an initiator to obtain the artificial SEI material;

[0008]

[0009] Among the R1 to R5, at least one substituent is a group containing a vinyl group at the end, and the remaining substituents are H, C1 to C6 alkyl, phenyl, substituted phenyl or benzyl;

[0010] The X is an anion;

[0011] Among the R6-R7, at least one substituent is a group containing a vinyl group at the terminal, and the remaining substituents are C1-C6 alkyl, phenyl, substituted phenyl or benzyl; or, R6 and R7 are cyclized to form a five-membered to six-membered ring with a monounsaturated double bond.

[0012] The present invention has found that the innovative use of monomers of formula 1 and formula 2 to initiate polymerization can construct a new polymer network, which unexpectedly has excellent high temperature resistance. Innovatively compounding it on the surface of the metal lithium negative electrode can increase the thermal runaway temperature and effectively improve the cycle stability of the metal lithium battery at high temperature.

[0013] In the present invention, the initiation polymerization of the monomers of Formula 1 and Formula 2 is the key to collaboratively constructing a special polymer network and improving the electrolyte stability and high temperature stability of the prepared SEI.

[0014] In the present invention, in the monomer of formula 1, preferably 1 to 2 of R1 to R5 are substituents containing a vinyl group at the terminal. In the monomer of formula 2, preferably 1 of R6 to R7 is a substituent containing a vinyl group at the terminal.

[0015] In the present invention, the group containing a vinyl group at the end is a vinyl group, an allyl group or an acryloyl group.

[0016] In the present invention, in the monomer of formula 1, R2, R3, and R5 are H or C1-C3 alkyl;

[0017] Preferably, R1 is vinyl or allyl; R4 is vinyl, allyl, or C1-C6 alkyl;

[0018] Preferably, the X- is at least one of a halogen ion, a tetrafluoroborate ion, and a bis(trifluoromethanesulfonyl)imide ion;

[0019] Preferably, the monomer of formula 1 includes at least one of formula 1-A, formula 1-B, and formula 1-C;

[0020]

[0021]

[0022] The R is a C1-C6 alkyl group;

[0023] Preferably, the monomers of formula 1 include formula 1-A and formula 1-B; more preferably, the molar ratio of formula 1-A to formula 1-B is 1:0.5 to 1. The present invention has found that the use of the combined monomers of formula 1 is helpful to further cooperate with the monomers of formula 2 to improve the polymer network structure and further improve the high temperature stability of the prepared metal lithium negative electrode.

[0024] In the present invention, the monomer of formula 2 includes at least one of formula 2-A, formula 2-B, and formula 2-C;

[0025]

[0026] The R is a C1-C6 alkyl group;

[0027] Preferably, the monomers of formula 2 include formula 2-B and formula 2-C; more preferably, the molar ratio of formula 2-B to formula 2-C is 0.5 to 1:1. The present invention has found that the use of the combined monomers of formula 2 is helpful to further cooperate with the monomers of formula 1 to improve the polymer network structure and further improve the high temperature stability of the prepared metal lithium negative electrode.

[0028] In the present invention, further controlling the ratio of monomers is helpful to further regulate the polymerization network, improve the high temperature performance of SEI, and improve the high temperature cycle stability of the composite metal lithium negative electrode.

[0029] Preferably, the molar ratio of the monomer of formula 1 to the monomer of formula 2 is 1-5:1-5; more preferably 1-2:1.

[0030] Preferably, the initiator is at least one of an azo initiator, a peroxide initiator, and a persulfate initiator; in the present invention, the azo initiator is, for example, azobisisobutyronitrile.

[0031] Preferably, the weight ratio of total monomers to initiator is 1:0.01 to 0.1; preferably 1:0.03 to 0.08;

[0032] Preferably, the polymerization reaction temperature is 40°C-80°C, preferably 45-70°C; more preferably 45-55°C.

[0033] Preferably, the polymerization process is carried out in a sealed pressure-resistant container;

[0034] Preferably, the polymerization reaction time is 6 to 12 hours, preferably 8 to 10 hours.

[0035] The present invention also provides an artificial SEI material prepared by the preparation method.

[0036] The present invention benefits from the initiation polymerization of the monomers of Formula 1 and Formula 2, and can construct a SEI polymer with a special structural network. The new SEI polymer network constructed by the preparation method unexpectedly has excellent high-temperature performance, which helps to improve the high-temperature cycle performance of the composite metal lithium negative electrode.

[0037] The present invention also provides an application of the artificial SEI material prepared by the preparation method, which is compounded on the surface of metallic lithium to prepare a lithium negative electrode for a metallic lithium battery.

[0038] The present invention also provides a composite metal lithium negative electrode, comprising a metal lithium active layer and an artificial SEI material layer prepared by the preparation method and in-situ composited on the surface of the metal lithium active layer.

[0039] The present invention has found that using the artificial SEI material layer to protect the metal lithium layer can effectively improve the performance of the metal lithium negative electrode, especially improve its electrochemical performance under harsh conditions (such as high temperature).

[0040] In the present invention, the metal lithium active layer may be a known one, for example, the metal lithium active layer is a metal lithium foil; or includes a current collector and metal lithium composited on its surface;

[0041] Preferably, the metal lithium active layer is a metal lithium foil; or comprises a current collector and metal lithium composited on its surface;

[0042] Preferably, the current collector is a planar metal current collector or a 3D current collector;

[0043] In the present invention, the thickness of the metal lithium active layer can be adjusted according to industry regulations, for example, between 5 μm and 500 μm.

[0044] In the present invention, the thickness of the artificial SEI film can be adjusted according to industry regulations, for example, the thickness is between 5 nm and 50 μm.

[0045] Preferably, the Young's modulus of the artificial SEI material layer is in the range of 500 MPa-10 GPa.

[0046] The present invention also provides a method for preparing a composite metal lithium negative electrode, wherein an in-situ polymerization reaction of a monomer of formula 1, a monomer of formula 2 and an initiator is carried out on the surface of a metal lithium active layer to form the artificial SEI material in-situ on the surface of the metal lithium active layer.

[0047] The invention also provides a lithium metal secondary battery, which contains the composite metal lithium negative electrode.

[0048] In the present invention, the lithium metal battery, except for the metal lithium negative electrode of the present invention, can have conventional materials and structures for other components.

[0049] The present invention utilizes monomers of formula 1, 2 and initiators to carry out heating polymerization reaction, which can effectively improve the stability of SEI film at high temperature, thereby improving the safety of the battery. In addition, the volume expansion of lithium metal during the cycle can be effectively alleviated, and the lithium-containing components of the interface layer can effectively even out the lithium ion flow, homogenize the migration of lithium ions, regulate the distribution of lithium ions on the negative electrode surface, avoid the aggregation of lithium ions in time and space, achieve the uniform distribution of lithium ions on the negative electrode surface, effectively isolate the direct contact between fresh metal lithium and electrolyte, reduce the side reactions caused by the contact between metal lithium and electrolyte, and improve the cycle coulomb efficiency of metal lithium secondary battery. The present invention has strong industrial feasibility and great industrial application value and potential. The metal lithium negative electrode prepared by the present invention has excellent cycle performance in all types of lithium batteries, and has good application prospects and universality in lithium secondary batteries.

[0050] Beneficial Effects

[0051] The present invention uses the monomer of formula 1, the monomer of formula 2 and the initiator to polymerize at the temperature to obtain a SEI film with good thermal stability. The SEI film is composited on the surface of metal lithium, which can unexpectedly synergistically improve the stability of the metal lithium negative electrode at high temperature.

[0052] Instruction Manual

[0053] Figure 1 This is a picture of the second solution of Example 1.

[0054] Figure 2 This is the ignition picture of the second solution prepared in Example 1. DETAILED DESCRIPTION

[0055] The following is a specific description of the preferred embodiments of the present invention, which does not constitute any limitation to the present invention. That is, the present invention is not meant to be limited to the above embodiments, and common modifications or alternative compounds in the technical field are all included in the scope defined by the claims of this application.

[0056] Embodiment 1:

[0057] Monomer of formula 1: Monomer 1:

[0058] Monomer of formula 2: Monomer 2:

[0059] 0.1 mol of monomer 1 is stirred at a temperature of 15°C to 25°C for 0.5 to 3 hours; when 0.1 mol of monomer 2 is added to monomer 1, it is stirred at a temperature of 15°C to 25°C for 0.5 to 2 hours to form a first solution; when azobisisobutyronitrile with a mass of 3% of the first solution is added to the first solution, it is stirred at a temperature of 0°C to 25°C for 0.5 to 2 hours to obtain a second solution, and the second solution exhibits non-flammable properties.

[0060] The second solution is heated to polymerize its components in situ, thereby obtaining a SEI film with good thermal stability. In this embodiment, in order to facilitate the subsequent battery assembly, the second solution is first coated on the lithium sheet, and then heated to polymerize its components in situ, so that the artificial SEI film with high thermal stability can be directly formed on the surface of the lithium sheet, the heating temperature is 50° C. (polymerization temperature), and the heating time is 10 hours.

[0061] The SEI film after in-situ polymerization can achieve good thermodynamic stability. A symmetrical battery was assembled with a lithium metal sheet. The electrolyte used was 1M LiTFSI / DOL:DME (volume ratio = 1:1) containing 1% wt LiNO3 as the electrolyte. 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button cell achieved 3000 cycles under 70℃ test conditions (the polarization voltage exceeded 1V as the termination condition; the same below), and the polarization voltage was only 20mV. Under the same test conditions, the blank lithium negative electrode without the modified layer coating could only maintain 500 cycles, and the polarization voltage was 100mV.

[0062] Example 2

[0063] Compared with Example 1, the only difference is that the initial content of monomer 1 in the second solution is 0.2 mol, and the second solution exhibits non-flammable properties. Electrochemical measurements were performed under the conditions described in Example 1. That is, at 1 mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 2800 cycles with a polarization voltage of only 20mV.

[0064] Example 3

[0065] Compared with Example 1, the only difference is that the initial content of monomer 2 in the second solution is 0.2 mol, and the second solution exhibits non-flammable properties. Electrochemical measurements were performed under the conditions described in Example 1. At 1 mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, 2032 button batteries were assembled and achieved 2400 cycles with a polarization voltage of 32mV.

[0066] Example 4

[0067] Compared with Example 1, the only difference is that the heating temperature (polymerization temperature) after the second solution is applied is 70° C., and the second solution exhibits a non-flammable property.

[0068] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 2400 cycles with a polarization voltage of only 26mV.

[0069] Example 5

[0070] Compared with Example 1, the only difference is that the heating temperature (polymerization temperature) after the second solution is applied is 40° C., the heating time is 12 h, and the second solution exhibits non-flammable characteristics.

[0071] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 2600 cycles with a polarization voltage of only 25mV.

[0072] Example 6

[0073] Compared with Example 1, the only difference is that the monomer 1 in the second solution is replaced by monomer 3:

[0074] The molar ratio of monomer 3 to monomer 2 is 1:1.

[0075] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 2200 cycles with a polarization voltage of only 35mV.

[0076] Example 7

[0077] Compared with Example 1, the only difference is that the monomer 2 in the second solution is replaced by the monomer 4 (Formula 2-B), and the molar ratio of the monomer 1 to the monomer 4 is 1:1.

[0078] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 2400 cycles with a polarization voltage of only 26mV.

[0079] Example 8

[0080] Compared with Example 1, the only difference is that a combination of monomer 1 and monomer 3 is used as the monomer of Formula 1; and in the second solution, the molar ratio of monomer 1:monomer 3:monomer 2 is 0.5:0.5:1. Other operations and parameters are the same as in Example 1.

[0081] The result is: at 1mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button cells achieved 3050 cycles with a polarization voltage of only 19mV.

[0082] Example 9

[0083] Compared with Example 1, the only difference is that a combination of monomer 2 and monomer 4 is used as the monomer of Formula 2; and in the second solution, the molar ratio of monomer 1:monomer 2:monomer 4 is 1:0.5:0.5. Other operations and parameters are the same as in Example 1.

[0084] The result is: at 1mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 3150 cycles with a polarization voltage of only 17mV.

[0085] Example 10

[0086] Compared with Example 1, the only difference is that a combination of monomer 1 and monomer 3 is used as the monomer of Formula 1; a combination of monomer 2 and monomer 4 is used as the monomer of Formula 2; and in the second solution, the molar ratio of monomer 1: monomer 3: monomer 2: monomer 4 is 0.5: 0.5: 0.5: 0.5. Other operations and parameters are the same as in Example 1.

[0087] The result is: at 1mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 3460 cycles with a polarization voltage of only 16mV.

[0088] By comparing Examples 8, 9 and 10 with Example 1, it is found that the use of combined monomers can unexpectedly further improve the high temperature cycle stability.

[0089] Comparative Example 1

[0090] Compared with Example 1, the only difference is that monomer 1 is not added, and the monomers all include monomer 2. Other operations and parameters are the same as in Example 1.

[0091] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 1200 cycles with a polarization voltage of only 29mV.

[0092] Comparative Example 2

[0093] Compared with Example 1, the only difference is that monomer 2 is not added, and the monomers all include monomer 1. Other operations and parameters are the same as in Example 1. The electrochemical measurement method of Example 1 is used, and the results are: at 1 mA / cm 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 1800 cycles with a polarization voltage of only 24mV.

[0094] Comparative Example 3

[0095] Compared with Example 1, the only difference is that the monomer 2 in the second solution is replaced by the comparative monomer A:

[0096] Other operations and parameters are the same as in Example 1.

[0097] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 1100 cycles with a polarization voltage of only 36mV.

[0098] Comparative Example 4

[0099] Compared with Example 1, the only difference is that the monomer 1 in the second solution is replaced by the comparative monomer B:

[0100] Other operations and parameters are the same as in Example 1.

[0101] The electrochemical measurement was carried out using the method of Example 1, and the results were as follows: 2 Charge and discharge current density and 1mAh / cm 2 Under the charge and discharge area capacity, the assembled 2032 button batteries achieved 1400 cycles with a polarization voltage of only 38mV.

Claims

1. A method for preparing an artificial SEI material, characterized in that: The monomers of formula 1 and formula 2 are polymerized in the presence of an initiator to obtain the artificial SEI material; Formula 1 Formula 2 Among the R1 to R5, at least one substituent is a group containing a vinyl group at the end, and the remaining substituents are H, C1 to C6 alkyl, phenyl, substituted phenyl or benzyl; The X is an anion; Among the R6~R7, at least one substituent is a group containing a vinyl group at the terminal, and the remaining substituents are C1~C6 alkyl, phenyl, substituted phenyl or benzyl; or, R6 and R7 are cyclized to form a five-membered to six-membered ring with a monounsaturated double bond.

2. The method for preparing an artificial SEI material according to claim 1, characterized in that: The group containing a vinyl group at the end is a vinyl group, an allyl group or an acryloyl group.

3. The method for preparing an artificial SEI material according to claim 2, characterized in that: In the monomer of formula 1, R2, R3, and R5 are H or C1-C3 alkyl; The R1 is vinyl or allyl; R4 is vinyl, allyl, or C1-C6 alkyl; The X- is at least one of a halogen ion, a tetrafluoroborate ion, and a bis(trifluoromethanesulfonyl)imide ion.

4. The method for preparing an artificial SEI material according to claim 1, characterized in that: The monomer of formula 1 includes at least one of formula 1-A, formula 1-B, and formula 1-C; Formula 1-A Formula 1-B Formula 1-C The R is a C1~C6 alkyl group.

5. The method for preparing an artificial SEI material according to claim 4, characterized in that: The monomers of formula 1 include those of formula 1-A and formula 1-B.

6. The method for preparing an artificial SEI material according to claim 5, characterized in that: The monomers of formula 1 are formula 1-A and formula 1-B in a molar ratio of 1:0.5~1.

7. The method for preparing an artificial SEI material according to claim 1, characterized in that: The monomer of formula 2 includes at least one of formula 2-A, formula 2-B, and formula 2-C; Formula 2-A Formula 2-B Formula 2-C The R is a C1~C6 alkyl group.

8. The method for preparing an artificial SEI material according to claim 7, characterized in that: The monomers of formula 2 include formula 2-B and formula 2-C.

9. The method for preparing an artificial SEI material according to claim 8, characterized in that: The monomers of formula 2 are formula 2-B and formula 2-C in a molar ratio of 0.5 to 1:

1.

10. The method for preparing an artificial SEI material according to any one of claims 1 to 9, characterized in that: The molar ratio of the monomer of formula 1 to the monomer of formula 2 is 1-5:1-5.

11. The method for preparing an artificial SEI material according to any one of claims 1 to 9, characterized in that: The initiator is at least one of an azo initiator, a peroxide initiator and a persulfate initiator.

12. The method for preparing an artificial SEI material according to claim 11, wherein: The weight ratio of total monomers to initiators is 1:0.01~0.

1.

13. The method for preparing an artificial SEI material according to claim 12, characterized in that: The weight ratio of total monomers to initiators is 1:0.03~0.

08.

14. The method for preparing an artificial SEI material according to claim 1, wherein: The polymerization temperature is 40°C-80°C.

15. The method for preparing an artificial SEI material according to claim 1, characterized in that: The polymerization process is carried out in a sealed pressure-resistant container.

16. The method for preparing an artificial SEI material according to claim 1, characterized in that: The polymerization reaction time is 6 to 12 hours.

17. An artificial SEI material obtained by the preparation method according to any one of claims 1 to 16.

18. An application of an artificial SEI material prepared by the preparation method according to any one of claims 1 to 16, characterized in that: It is compounded on the surface of metallic lithium and used to prepare the lithium negative electrode of metallic lithium battery.

19. A composite metal lithium negative electrode, characterized in that: The invention comprises a metal lithium active layer and an artificial SEI material layer which is in-situ composited on the surface thereof and is prepared by the preparation method according to any one of claims 1 to 16.

20. The composite metal lithium negative electrode according to claim 19, characterized in that: The metal lithium active layer is a metal lithium foil; or includes a current collector and metal lithium compounded on its surface.

21. The composite metal lithium negative electrode according to claim 20, characterized in that: The current collector is a planar metal current collector or a 3D current collector.

22. The composite metal lithium negative electrode according to claim 19, characterized in that: The thickness of the artificial SEI material layer is between 5 nm and 50 μm.

23. The composite metal lithium negative electrode according to claim 19, characterized in that: The Young's modulus of the artificial SEI material layer ranges from 500 MPa to 10 GPa.

24. A method for preparing a composite metal lithium negative electrode, characterized in that: By using the preparation method described in any one of claims 1 to 16, an in-situ polymerization reaction of the monomer of formula 1, the monomer of formula 2 and the initiator is carried out on the surface of the metal lithium active layer to form the artificial SEI material in situ on the surface of the metal lithium active layer.

25. A lithium metal secondary battery, characterized in that: A composite metal lithium negative electrode comprising the composite metal lithium negative electrode as described in claim 19 or the composite metal lithium negative electrode prepared by the preparation method as described in claim 24.

Citation Information

Patent Citations

  • Method for producing vinylamine by kettle-type reactor

    CN103130651A

  • Three-dimensional porous metal lithium negative electrode for secondary battery and preparation and application thereof

    CN111799443A